2019
DOI: 10.4103/jfmpc.jfmpc_67_19
|View full text |Cite
|
Sign up to set email alerts
|

Communicable or noncommunicable diseases? Building strong primary health care systems to address double burden of disease in India

Abstract: Between 1990 and 2016, India has seen an epidemiological transition in disease burden and deaths, with a steady rise in noncommunicable disease (NCD) burden. This has led to a tussle for policy attention and resources between proponents of communicable diseases such as tuberculosis, and of NCDs, such as cardiovascular diseases and diabetes. Review of evidence from global burden of diseases studies and from our own field data from rural south Rajasthan reveals that communicable-malnutrition- maternal-newborn di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 7 publications
1
34
0
2
Order By: Relevance
“…In India, rapid nutritional and epidemiological transition has affected the health status in both urban and rural areas. More importantly, rural populations are burdened with existing communicable diseases as well as emerging lifestyle and noncommunicable disorders (Mohan et al, 2019a). It is important to assess the emerging lifestyle disorders among children and adolescents because their health status is significantly correlated with adult well-being or diseases burden.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In India, rapid nutritional and epidemiological transition has affected the health status in both urban and rural areas. More importantly, rural populations are burdened with existing communicable diseases as well as emerging lifestyle and noncommunicable disorders (Mohan et al, 2019a). It is important to assess the emerging lifestyle disorders among children and adolescents because their health status is significantly correlated with adult well-being or diseases burden.…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that almost half of adults with hypertension had elevated BP during childhood and adolescence (Bao et al, 1995; Chen & Wang, 2008) with studies indicating child and adolescent hypertension correlated with adult vascular damage and atherosclerosis (Hartiala et al, 2012; Li et al, 2003). In India, previous studies have reported varying prevalence of hypertension in children and adolescents, ranging from <1% to 16.2% (Mohan et al, 2019b). Despite high prevalence of hypertension among children and adolescents, physicians often do not recognize the condition; BP measurement is a neglected part of physical examination among children and adolescents, with most of the prevention and control strategies targeting adults.…”
Section: Introductionmentioning
confidence: 99%
“…This finding implies that that there is a “gap” in healthcare provision for NCDs that is currently not being addressed adequately—despite evidence of increasing burden. [3031]…”
Section: Discussionmentioning
confidence: 99%
“…The state is one of the backward states, comes under Empowered Action Group States (EAG) states ii , and is lagging behind on several human development indicators compared to the national average (17). The dual burden of communicable and non-communicable diseases is also a major concern for Rajasthan [18, 19]. Although there is no latest available data to understand the situation of the health system in Rajasthan the data available as of 2012-13 highlights major gap in human resource and infrastructure in primary health care facilities [20].…”
Section: Introductionmentioning
confidence: 99%